The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1160/th03-02-0123
|View full text |Cite
|
Sign up to set email alerts
|

Human platelets contain forms of factor V in disulfide-linkage with multimerin

Abstract: Factor V is an essential cofactor for blood coagulation that circulates in platelets and plasma. Unlike plasma factor V, platelet factor V is stored complexed with the polymeric alpha-granule protein multimerin. In analyses of human platelet factor V on nonreduced denaturing multimer gels, we identified that approximately 25% was variable in size and migrated larger than single chain factor V, the largest form in plasma. Upon reduction, the unusually large, variably-sized forms of platelet factor V liberated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Plasma was tested for IgG autoantibodies against FV, as previously described [8]. Plasma and platelet lysates were tested by: FV ELISA (using detecting antibodies against heavychain, light-chain, and B-domain epitopes) [12]; western blotting (using polyclonal antisera after reduced sodium dodecylsulfate polyacrylamide gel electrophoresis) [13]; and MMRN1 and FV-MMRN1 complex ELISA [12]. CAT was used to test FVa-dependent thrombin generation by plateletpoor plasma (PPP), platelet-rich plasma (PRP), and washed platelets [14], resuspended in control, patient or FV-deficient plasma (final in assay: 135 · 10 9 platelets L -1…”
mentioning
confidence: 99%
“…Plasma was tested for IgG autoantibodies against FV, as previously described [8]. Plasma and platelet lysates were tested by: FV ELISA (using detecting antibodies against heavychain, light-chain, and B-domain epitopes) [12]; western blotting (using polyclonal antisera after reduced sodium dodecylsulfate polyacrylamide gel electrophoresis) [13]; and MMRN1 and FV-MMRN1 complex ELISA [12]. CAT was used to test FVa-dependent thrombin generation by plateletpoor plasma (PPP), platelet-rich plasma (PRP), and washed platelets [14], resuspended in control, patient or FV-deficient plasma (final in assay: 135 · 10 9 platelets L -1…”
mentioning
confidence: 99%
“…The recombinant MMRN1 contained 18.5 g of MMRN1 per unit of antigen (amount contained in 10 9 pooled normal platelets) (10). Because of variability in MMRN1 polymer size, molar concentrations of recombinant MMRN1 were calculated based on the amounts of MMRN1 subunits (average subunit size was 186 kDa).…”
Section: Methodsmentioning
confidence: 99%
“…Third, after conversion of factor V to Va, there was a considerable (84%) reduction in binding of liberated B domain fragments to MMRN1. Recently, we identified that human platelets contain forms of factor V that are linked to MMRN1 by a disulfide bridge involving cysteine 1085 in the factor V B domain (10). Although it is possible that the B domain enhances factor V-MMRN1 binding indirectly by altering conformation of the factor V light chain, the covalent linkages between the factor V B domain and MMRN1 in platelets suggests that the B domain directly contributes to the MMRN1 binding site of factor V.…”
Section: Fig 2 Binding Of Mmrn1 To Constructs With Mutated Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In blood, approximately 25% of the factor V (FV) is retained in platelet α-granules, where FV is stored as a partially activated cofactor complexed to the polymeric protein multimerin 1 (MMRN1) [2,3]. In humans, MMRN1-FV binding is predominantly noncovalent, although 25% of platelet FV is disulfide linked to MMRN1 [3]. Noncovalent FV-MMRN1 binding involves an extended region of the FV light chain C2 domain, that overlaps the FVa membrane binding site [4].…”
mentioning
confidence: 99%